Brief Report: Blood and Genital Fluid Viral Load Trajectories Among Treated and Untreated Persons With Acute HIV Infection in Malawi. (1st May 2022) - Chen, Jane S.; Pettifor, Audrey E.; Nelson, Julie A.E.; Phiri, Sam; Pasquale, Dana K.; Kumwenda, Wiza; Kamanga, Gift; Cottrell, Mackenzie L.; Sykes, Craig; Kashuba, Angela D.M.; Tegha, Gerald; Krysiak, Robert; et al.
Abstract : Background: Persons with acute HIV infection (AHI) are highly infectious and responsible for a disproportionate share of incident infections. Immediate antiretroviral therapy (ART) rapidly reduces blood viral loads (VLs), but genital VLs after ART initiation during AHI are less well described. Setting: Lilongwe, Malawi, 2012–2014. Methods: HIV-seronegative and HIV-serodiscordant persons aged ≥18 years were screened for AHI (RNA positive) and randomized to standard of care, behavioral intervention, or behavioral intervention plus short-term ART (raltegravir/emtricitabine/tenofovir) (1:2:2). Persons who were ART eligible under Malawi guidelines could receive first-line therapy. Blood and genital VLs were assessed at weeks 1, 4, 8, and 12. Fisher's Exact test was used to compare viral suppression by ART status. Results: Overall, 46 persons with AHI were enrolled; of whom, 17 started ART within 12 weeks. Median blood VL at AHI diagnosis was 836, 115 copies/mL. At week 12, 7% (1/14) of those who initiated ART had a blood VL of ≥400 copies/mL, compared with 100% (23/23; P < 0.0001) of those who did not initiate ART (median VL: 61, 605 copies/mL). Median genital VL at week 1 was 772 copies/mL, with 13 of 22 (59%) having VL of ≥400 copies/mL. At week 12, 0 of 10 (0%) of those who initiated ART had genital VL of ≥400 copies/mL, compared with 7 of 15 (47%) of those who did not initiate ART ( P = 0.02). Conclusion: Although highly correlated, VLs in blood and genital fluids occupy discrete biological compartments with distinct virologic dynamics. Our results corroborate the dramatic reduction in both compartments after ART initiation. Increasing AHI screening and rapidly initiating treatment is key to interrupting transmission.